Enhancing the Performance Commitment of the Task Force for the Prevention and Handling of Sexual Violence through an Organizational Leadership Approach at the Academy of Hospital Administration Mataram - Syatriawan Perdana Putra; I Made Putu Sudiartha Hartawan (Dinasti International Journal of Education Management and Social Science, 2025)
Sexual violence in academic settings has become a serious concern, and the role of the Task Force for the Prevention and Handling of Sexual Violence in Higher Education (PPKPT) at the Academy of Hospital Administration Mataram (AARS) is particularly crucial. This study aims to offer a solution by employing an Organizational Leadership approach as a key strategy to strengthen the performance commitment of the task force. A qualitative descriptive method was applied, with data collected through three stages: (1) participatory observation, (2) interviews and documentation, (3) focus group discussions (FGDs). Data analysis followed several steps, including data reduction, data presentation, source triangulation, and conclusion drawing. The findings indicate that: (1) the Organizational Leadership approach plays a strategic role in enhancing the performance commitment of the PPKPT task force at AARS through visionary, communicative, and supportive leadership that fosters emotional engagement, moral responsibility, and member motivation; (2) the performance commitment of the task force is currently at a consolidation stage, marked by active involvement of some members in reporting and socialization, although improvements are still needed in participation, technical understanding, and self-confidence; and (3) effective leadership strategies include: (a) a clear and inspiring vision, (b) open and regular communication, and (c) continuous motivation and recognition. By optimizing these strategies, the PPKPT task force is expected to perform its duties more effectively in preventing and responding to sexual violence while supporting the achievement of the institution’s vision and mission.